The dexmedetomidine concentration required after remifentanil anesthesia is three-fold higher than that after fentanyl anesthesia or that for general sedation in the ICU - Kunisawa T; Fujimoto K; Kurosawa A; Nagashima M; Matsui K; Hayashi D; Yamamoto K; Goto Y; Akutsu H; Iwasaki H (Dove Medical Press, 2014)
Takayuki Kunisawa,1 Kazuhiro Fujimoto,2 Atsushi Kurosawa,2 Michio Nagashima,2 Koji Matsui,2 Dai Hayashi,2 Kunihiko Yamamoto,2 Yuya Goto,2 Hiroaki Akutsu,3 Hiroshi Iwasaki21Surgical Operation Department, Asahikawa Medical University Hospital, 2Department of Anesthesiology and Critical Care Medicine, 3Central Laboratory for Research and Education, Asahikawa Medical University, Asahikawa, Hokkaido, JapanPurpose: The general dexmedetomidine (DEX) concentration required for sedation of intensive care unit patients is considered to be approximately 0.7 ng/mL. However, higher DEX concentrations are considered to be required for sedation and/or pain management after major surgery using remifentanil. We determined the DEX concentration required after major surgery by using a target-controlled infusion (TCI) system for DEX.Methods: Fourteen patients undergoing surgery for abdominal aortic aneurysms (AAA) were randomly, double-blindly assigned to two groups and underwent fentanyl- or remifentanil-based anesthetic management. DEX TCI was started at the time of closing the peritoneum and continued for 12 hours after stopping propofol administration (M0); DEX TCI was adjusted according to the sedation score and complaints of pain. The doses and concentrations of all anesthetics and postoperative conditions were investigated.Results: Throughout the observation period, the predicted plasma concentration of DEX in the fentanyl group was stable at approximately 0.7 ng/mL. In contrast, the predicted plasma concentration of DEX in the remifentanil group rapidly increased and stabilized at approximately 2 ng/mL. The actual DEX concentration at 540 minutes after M0 showed a similar trend (0.54±0.14 [fentanyl] versus 1.57±0.39 ng/mL [remifentanil]). In the remifentanil group, the dopamine dose required and the duration of intubation decreased, and urine output increased; however, no other outcomes improved.Conclusion: The DEX concentration required after AAA surgery with remifentanil was three-fold higher than that required after AAA surgery with fentanyl or the conventional DEX concentration for sedation. High DEX concentration after remifentanil affords some benefits in anesthetic management.Keywords: plasma concentration, effect-site concentration (ESC), target-controlled infusion (TCI), abdominal aortic aneurysms (AAA), dopamine, urine output